1998
DOI: 10.3109/10837459809028500
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Sucrose/Glycine/ Water System by Differential Scanning Calorimetry and Freeze-Drying Microscopy

Abstract: The objective of this study was to characterize the thermal properties of systems containing various ratios of amorphous and crystalline components using both differential scanning calorimetry (DSC) and freeze-drying microscopy. The glycine/sucrose system was used as a model system, since it is routinely used in protein formulations. DSC analysis revealed that the addition of glycine to sucrose solutions resulted in a decrease in the glass transition (T'g) of the system. The T'g of a pure sucrose solution (7% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 6 publications
3
29
0
Order By: Relevance
“…The T g ' of sucrose is reported as À328C. 22 However, it has been reported that adding increasing amounts of protein to most formulations leads to a higher T c and T g ', 1,21 and, importantly in the context of this work, the difference between T g ' and T c (T c ¼ the temperature at which the freeze-drying front completely collapses) 12 can increase at increasing higher protein loadings. 1,18,23 The T g ' and T c of the sucrose-containing protein formulations in this study is À33 and À288C for the 5 mg mL À1 BSA formulation and À26 and À98C for the 50 mg mL À1 BSA formulation respectively.…”
Section: Resultsmentioning
confidence: 80%
“…The T g ' of sucrose is reported as À328C. 22 However, it has been reported that adding increasing amounts of protein to most formulations leads to a higher T c and T g ', 1,21 and, importantly in the context of this work, the difference between T g ' and T c (T c ¼ the temperature at which the freeze-drying front completely collapses) 12 can increase at increasing higher protein loadings. 1,18,23 The T g ' and T c of the sucrose-containing protein formulations in this study is À33 and À288C for the 5 mg mL À1 BSA formulation and À26 and À98C for the 50 mg mL À1 BSA formulation respectively.…”
Section: Resultsmentioning
confidence: 80%
“…18 As pointed out earlier, analysis of lyophiles of pure glycine, as well as sucrose-glycine mixtures by XRD, confirmed that b-glycine was the only crystalline polymorph present. a-Glycine and g-glycine were absent in all the samples.…”
Section: Subtraction Of Glycine Signals From Protein Amide I Spectramentioning
confidence: 72%
“…In a few cases, both T c and T 0 g values for excipients or a final formulation are reported. 9,31 An important observation for freezedrying cycle design is that collapse temperatures have been reported 2-58C above the corresponding T 0 g for various systems; 19 in short, the two methods do not necessarily measure the same property, and the difference is not negligible. In addition, information about the temperature ''tolerance'' of a given product to product temperature excursions exceeding the predefined critical temperature is helpful for robustness testing in process design, but such data are typically not available in the literature.…”
Section: Introductionmentioning
confidence: 99%